Kemampuan pemahaman konsep: Pengaruh pembelajaran CTL pada materi penjumlahan dan pengurangan pecahan - Mudrikah, Firdaul; Yunita Sari, Filian (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2025)
A strong grasp of mathematical concepts is fundamental for developing problem-solving abilities. Yet, many fifth-graders struggle to master fraction operations, particularly addition and subtraction. This research investigates the efficacy of the Contextual Teaching and Learning (CTL) model in enhancing students' conceptual mastery of mathematics. Utilizing a quasi-experimental quantitative design, the study was implemented at SDN 1 Number Sari, with participants selected via cluster random sampling—12 students in the experimental group and 16 in the control group. Data were gathered through conceptual understanding assessments and documentary analysis. The t-test revealed statistically significant outcomes (p= 0.017), while the effect size (d= 0.83) indicated a substantial practical impact, classifying CTL as highly effective. These findings demonstrate that CTL not only achieves statistical significance but also delivers meaningful educational improvements. Thus, CTL proves to be a powerful pedagogical strategy for advancing fifth-grade students’ comprehension of fractional operations.